The design thinking quick start guide : a 6-step process for generating and implementing creative solutions - Osann, Isabell; Mayer, Lena; Wiele, Inga (John Wiley & Sons, Inc., 2020)
"Apply Design Thinking and lead teams to new solutions in 6 steps. What is creativity? How do you become creative? The Design Thinking Quick Start Guide answers these questions and presents the methods needed to start being creative and coming up with new ideas in a playful way. From the 6-3-5 method to brainstorming, you will find methods for generating ideas within the pages of this book. The Design Thinking Quick Start Guide provides checklists, procedures and techniques for brainstorming and implementation, so you reach your goal creatively. For each of the 6 phases, the authors present two warm-ups, to prepare the team for the work ahead. Whether you are a newcomer or experienced with Design Thinking? you are sure to find inspiration for your next team meeting here"--